Launching new ventures an entrepreneurial approach - Allen, Kathleen R. (Cengage Learning, 2016)
This text provides tomorrow's entrepreneurs with the tools to launch a successful new business in a global marketplace. The text follows the logical development process: from initial idea, to developing and testing a business model, to designing a business and preparing for growth. The seventh edition represents the most current thoughts, ideas, and practices in the field of entrepreneurship. Allen focuses on the pre-startup and startup stages of a new business, with special emphasis on the process and activities that must take place prior to opening a new business. The student-friendly material includes real-world case studies, new venture action plans, and advice from successful entrepreneurs.